Taking of hostages as an offense in international law and Serbian regulations - Cmiljanić Bajo M. (Temida)
In the development of international relations, hostage-taking was carried out as an insurance against fraud, not keeping obligations, or according to the rules of war law. Earlier taking hostages was more related to armed conflicts, and in modern times it is more related to terrorist acts in international terrorism. The taking of hostages is an international offense, which has its essential elements and characteristics. It is a crime punishable under the national legislation of many countries, and taking of hostages in armed conflicts is a war crime for which the International Criminal Court is responsible. International terrorism is manifested through a variety of terrorist acts, which, through fear and panic aim to achieve a political purpose. The range of these terrorist acts is wide and varied. One of these terrorist activities is the taking of hostages. As an offense established by the norms of international law, this unlawful act must be specifically investigated and clarified, which is the goal of this paper. This paper gives an overview of the features and elements of the offense in the light of international law and the laws of the Republic of Serbia.